2005
DOI: 10.1029/2004ja010715
|View full text |Cite
|
Sign up to set email alerts
|

AE index variability during corotating fast solar wind streams

Abstract: [1] We examine the AE index variability while 12 corotating fast solar wind streams pass the Earth during the ascending phase of the ongoing solar activity cycle. We apply the Discrete Fourier Transform analysis to the associated interplanetary magnetic field (B) data and AE time series with $1 min resolution. Results show noticeable periodicities in the 1-10 hour range. Moreover, the B and AE periodicities in each event are well correlated. For this reason a direct relationship between interplanetary Alfvénic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…[11] Our definition of high-speed streams in this paper is solar wind streams with V sw > 500 km/s that are not associated with a CME. We have confirmed the earlier result [e.g., Sheeley et al, 1977;Diego et al, 2005;Tanskanen et al, 2005] that the occurrence of high-speed streams and their accompanied Alfvén waves are not limited to the declining phase of the solar cycle but can also exist during other years, although they are less frequent and of shorter duration. We searched for high-speed streams and their associated Alfvén waves for the period 1996-2002.…”
Section: High-speed Streams Alfvénic Fluctuations Of Imf and Repetisupporting
confidence: 91%
See 1 more Smart Citation
“…[11] Our definition of high-speed streams in this paper is solar wind streams with V sw > 500 km/s that are not associated with a CME. We have confirmed the earlier result [e.g., Sheeley et al, 1977;Diego et al, 2005;Tanskanen et al, 2005] that the occurrence of high-speed streams and their accompanied Alfvén waves are not limited to the declining phase of the solar cycle but can also exist during other years, although they are less frequent and of shorter duration. We searched for high-speed streams and their associated Alfvén waves for the period 1996-2002.…”
Section: High-speed Streams Alfvénic Fluctuations Of Imf and Repetisupporting
confidence: 91%
“…These fluctuations have large amplitudes during the periods of high-speed solar wind. Other examples of similar fluctuations have been shown to be Alfvén waves [e.g., Tsurutani et al, 1995a;Diego et al, 2005]. The IMF B z fluctuates roughly between +5 and À5 nT.…”
Section: High-speed Streams Alfvénic Fluctuations Of Imf and Repetimentioning
confidence: 78%
“…The fluctuations of the interplanetary magnetic field during fast streams have been shown to be mostly due to Alfvén waves propagating outward from the Sun. Previous studies suggested that there is a close correlation between interplanetary Alfvén waves and AE index [ Gonzalez et al , 1999; Diego et al , 2005; Chian et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the ring current effect in the storm time depression is controversial with the estimates of the symmetric ring current contribution to Dst ranging from 0 to 40%, and the contributions of the crosstail and partial ring current to Dst are very discrepant with the corresponding estimates varying from 15/25 to 80% (Maltsev, 2003). Moreover, the Physics of the associated storm-substorm relationship is presently poorly understood (e.g., Diego et al, 2005, and references therein).…”
Section: Discussionmentioning
confidence: 92%